A NEW SPECIES OF THE DEVONIAN ACTINOPTERYGIAN FISH MOYTHOMASIA FROM BELARUS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
A new species of early actinopterygian fishes, Moythomasia lebedevi sp. nov., is described based on numerous isolated scales occurring in Middle Devonian (Givetian, Polotskian Regional Stage) marine deposits (Goryn, Stolin and Moroch Beds) of Belarus. These scales characterize different ontogenetic stages (adult and subadult) of the fish. Few additional scales from Upper Devonian (Famennian) marine deposits of Russia (Perm Krai) are attributed to Moythomasia cf. lebedevi sp. nov. based on the ornamentation, scale shape, and the type of scale-to-scale articulation. The new data add to our knowledge on the taxonomic composition of the Givetian and Famennian ichthyofaunas of the East European platform.
Keywords: Actinopterygii; ganoid scales; Moythomasia lebedevi sp. nov.; Devonian, Belarus, Russia.